Perancangan Antarmuka Pengguna Sistem Portofolio Siswa Sekolah Sepak Bola (SSB) Sumbersari Menggunakan Metode Design Thinking - Yogie Tegar Pribadi; Buce Trias Hanggara; Bonda Sapta Prakoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Sumbersari Football School is an informal school that focuses on soccer for students aged 7 to 14 years. This soccer school has several problems in the training it runs. The problems experienced include the absence of student portfolio data during the exercise. Based on the problems experienced by SSB Sumbersari, interviews were conducted to explore the needs and what were the core problems. The purpose of this research is to find a solution to the problems currently being experienced by SSB Sumbersari. Solutions to problems experienced, SSB Sumbersari requires a design design for the student portfolio system. At the stage of extracting the needs, 4 user needs and 7 solution ideas have been made. In designing this student portfolio design using the design thinking method. The final result of this research according to the results of the System Usability Scale gets a value of 78 which is included in the good category.